2006
DOI: 10.1021/jp056981p
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Structure and Dynamics in Aqueous Electrolytes at Ambient and Supercritical Conditions

Abstract: Hydrogen bond (HB) connectivity in aqueous electrolyte solutions at ambient and supercritical conditions has been investigated by molecular dynamics techniques. Alkali metal and halides with different sizes have been considered. Modifications in the water HB architecture are more noticeable in the first ionic solvation shells and do not persist beyond the second shells. The coordination pattern is established between partners located in the first and second solvation shells. High-temperature results show drama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
94
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 56 publications
15
94
1
Order By: Relevance
“…The correlation times were reported to be 20 to 50 times longer than those of pure water. MD simulations on halide-water systems suggested that the very long correlation times measured by two-color pump-probe experiments were similar to residence times of water molecules in the first hydration shells of halide anions in dilute solutions (30,(47)(48)(49). However, there is no bulk water in the highly concentrated salt solutions, and, as shown in previous studies of various water systems (5)(6)(7)18), the FFCFs of water are nonexponential in nature and decays on multiple time scales.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The correlation times were reported to be 20 to 50 times longer than those of pure water. MD simulations on halide-water systems suggested that the very long correlation times measured by two-color pump-probe experiments were similar to residence times of water molecules in the first hydration shells of halide anions in dilute solutions (30,(47)(48)(49). However, there is no bulk water in the highly concentrated salt solutions, and, as shown in previous studies of various water systems (5)(6)(7)18), the FFCFs of water are nonexponential in nature and decays on multiple time scales.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, MD simulations performed on ionicsolution, hydrogen-bond lifetime correlation functions were calculated (48,49). These simulations show that the lifetime of water-Br Ϫ hydrogen bonds is a few picoseconds and is somewhat longer than that of water-water hydrogen bonds (49).…”
Section: Discussionmentioning
confidence: 99%
“…We now mention two other recent studies whose conclusions are broadly in line with those of Omta et al (Omta et al, 2003). Guardia et al (Guardia et al, 2006) carried out extensive molecular dynamics simulations of aqueous alkali metal and halides at ambient and supercritical conditions to explore the effects of ions on the intermolecular connectivity of water in the close vicinity of solutes. From a dynamical perspective, the most relevant feature was that the lifetimes of hydrogen bond do not seem to be affected in an appreciable manner by the presence of ions.…”
Section: Structure Of Water Near Ionssupporting
confidence: 63%
“…At this point it has to be mentioned that very similar geometric criteria have been successfully used in the past to predict the HB properties of water and alcohols 9,[31][32][33][34][35][36][37][38][39][40][41][42][43] . Using this simple geometric criterion, the calculated average number of hydrogen bonds per water molecule < n HB > has been estimated to be 3.48, in agreement with the value of 3.58 obtained by reverse modelling of neutron diffraction data 44 .…”
Section: A Local Structure -Hb Networkmentioning
confidence: 99%